Analysis of Strength Stiffness and Modes for Bus Body Frame. Issue 6 (January 2021) - Yao, Chunge; Yang, Mengjie
Abstract: In this paper, the bus body frame is made as a research object. The finite element model of bus body frame is built in Hypermesh software. The static strength and stiffness of bus body frame under four typical working conditions are calculated by Nastran solver. Modal analysis is carried out by Lanczos method, low natural frequency and vibration mode are obtained. The analysis of results show that the strength and stiffness of bus body frame must meet design requirement, and the modal frequency is also within the design range. According to finite element analysis, the development cycle of new product is reduced, and theoretical basis for later model improvement and optimal design is provided.